2022
DOI: 10.7759/cureus.25907
|View full text |Cite
|
Sign up to set email alerts
|

Elevated International Normalized Ratio Due to Apixaban in Patient With End-Stage Renal Disease on Hemodialysis

Abstract: Apixaban is known to prolong international normalized ratio (INR) per some observational and in vitro studies. In patients with elevated INR secondary to apixaban use, median INR of 1.4-1.7 has been reported. Extreme elevation in INR is rare with apixaban. In patients with end-stage renal disease (ESRD) on hemodialysis (HD), there are no labeled indications for apixaban use; however, there are some pharmacokinetic data supporting its use in such patients. We present a case of a 68-year-old Hispanic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some causes of LR have been reported in previous reports, which indicated that LR can be caused by severe infection, malignancies, intoxication, severe hemorrhage, or acute hemolysis [3]; LR can lead to a very severe prognosis [4][5][6]. Furthermore, only a few reports suggest that it also occurs under stressful conditions, resulting in multi-organ failure [7][8][9][10]. Although severe heart failure requiring mechanical circulatory support (MCS) is a severely stressful condition, there are no reports suggesting an association between LR and severe heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Some causes of LR have been reported in previous reports, which indicated that LR can be caused by severe infection, malignancies, intoxication, severe hemorrhage, or acute hemolysis [3]; LR can lead to a very severe prognosis [4][5][6]. Furthermore, only a few reports suggest that it also occurs under stressful conditions, resulting in multi-organ failure [7][8][9][10]. Although severe heart failure requiring mechanical circulatory support (MCS) is a severely stressful condition, there are no reports suggesting an association between LR and severe heart failure.…”
Section: Introductionmentioning
confidence: 99%